We have a 45-45-90 triangle with hypotenuse
![24 √(6) \: \: \: leg \: x \: therefore \: has \: length \\ (24 √(6) )/( √(2 \:) \: ) \: = \: (24 √(3) √(2) )/( √(2) \: ) = 24 √(3) = x \\ \\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y9g1d9hjarcun56vfvv4zp2d8mbylyimov.png)
We now work with the 30-60-90. triangle having a side opposite the 60 degree angle of length
![24 √(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pns5p15cu95r8rvxcmkqas12ej3ccwtwgo.png)
y, the side opposite the 30 degee angle then has length
![(24 √(3) )/( √(3)) = 24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fgoq23kplok43vrl1pnys1vrloo4a5omoh.png)
The hypotenuse has length twice the side opposite the 30 degree angle = 2y = 48 = z